Highly Ordered Structure Formation in RAFT‐Synthesized PtBOS‐b‐P4VP Diblock Copolymers. Issue 11 (15th April 2016) - Faber, Martin; Hofman, Anton H.; Loos, Katja; Brinke, Gerrit ten
Abstract : Linear poly(4‐ tert ‐butoxystyrene)‐ b ‐poly(4‐vinylpyridine) (P t BOS‐ b ‐P4VP) diblock copolymers are synthesized using reversible addition–fragmentation chain transfer polymerization. The self‐assembly of four different P t BOS‐ b ‐P4VP diblock copolymers is studied using small‐angle X‐ray scattering and transmission electron microscopy and a number of interesting observations are made. A t BOS62 ‐ b ‐4VP28 diblock copolymer with a weight fraction P4VP of 0.21 shows a disordered morphology of P4VP spheres with liquid‐like short‐range order despite an estimated value of χ N of the order of 50. Increasing the length of the 4VP block to t BOS62 ‐b‐4VP199 results in a diblock copolymer with a weight fraction P4VP of 0.66. It forms a remarkably well‐ordered lamellar structure. Likewise, a t BOS146 ‐ b ‐4VP120 diblock copolymer with a weight fraction P4VP of 0.33 forms an extremely well‐ordered hexagonal structure of P4VP cylinders. Increasing the P4VP block of this block copolymer to t BOS146 ‐ b ‐4VP190 with a weight fraction P4VP of 0.44 results in a bicontinuous gyroid morphology despite the estimated strong segregation of χ N ≅ 150 . These results are discussed in terms of the architectural dissimilarity of the two monomers, characterized by the presence of the large side group of P t BOS, and the previously reported value of the interaction parameter, χ ≅ 0.39, for this polymer pair. Abstract : Four linear poly(4‐tert‐butoxystyrene)‐b‐poly(4‐vinylpyridine) diblock copolymers are synthesized using reversible addition–fragmentation chain transfer polymerization and their self‐assembly studied using small‐angle X‐ray scattering and transmission electron microscopy. Although a micellar morphology is observed for the diblock with the lowest weight fraction P4VP, remarkably well‐ordered lamellae, hexagonally packed cylinders and a bicontinuous gyroid appear in the copolymers richer in P4VP.